E-COMMERCE PLATFORM ECOSYSTEM WITH STRATEGIC MANAGEMENT POINT OF VIEW â CASE STUDY OF E-COMMERCE IN INDONESIA - Amalyah agus, Anna
By using Indonesian E-commerce platform case studies as proxy of countries with high growth on e-commerce and omni-channel distribution, this research plan to fill the research gap in the theories of transaction cost economics, multi-attribute utility theory, agency theory and information-processing theory, through variable based modeling. For business and industry stakeholder point of view, this research is expected to be useful for Indonesian e-commerce platform ecosystem stakeholders especially regulators, to give insights towards key success factors and dynamics within e-commerce platform ecosystem. This research originality lies on proposing e-commerce conceptual model by using multidisciplinary approach through combining four main constructs, which consists of relative e-commerce platform performance, digital marketing capability, customer experience review rating and supply chain capabilities. The model also accommodates seasonal pricing and logistic outsourcing as intervening variables to examine model sensitivity. Before covid 19 outbreak, this research collected 1288 end-consumer (B2C consumer) who have purchased items in at least two e-commerce platform and 308 e-commerce seller (B2B consumers) within e-commerce platform. After Covid 19 outbreak, there are 88 B2C consumer and 55 B2B consumer called back data. Collected data is processed using Structural Equation Modeling (SEM) method by LISREL software and multivariate statistics using SPSS. The modelling results demonstrate that digital promotion capability, customer review rating and seasonal pricing giving positive impact to e-commerce platform performance. Meanwhile, intervening effect of logistics outsourcing toward supply chain capabilities could lead to negative impacts on e-commerce performance. There are slight differences especially in digital promotion capabilities and supply chain capabilities before and after Covid 19 outbreak. The findings suggest 4 managerial implications 1) having strong digital promotion capabilities is a must to increase e-commerce platform performance, 2) combination of digital promotion and seasonal pricing will strengthen e-commerce performance, 3) maintaining positive consumer experience/review rating will also increase e-commerce performance, 4) having reliable third party logistic partner will create positive supply chain capability that lead to better performance.